Antibacterial Activity of Streptomyces sp. NrASA6 Culture Extract Isolated from Nypa Palm Worm Substrate against Escherichia coli, Staphylococcus aureus, and Aeromonas sp. NrBF9 - Henno Wisnu Putra; Kurniatuhadi, Rikhsan; Tri Rima Setyawati; Ari Hepi Yanti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Aquaculture is an effort to maintain aquatic commodities aimed at increasing cultivation. Probiotics are one of the components needed to serve as food additives that can prevent pathogenic bacterial infections in animals. One of the Actinomycetes species that has the potential to be used as a probiotic is Streptomyces sp. These species are known to be able to inhibit patogenic bacterial infections. The purpose of this research is to know about the antibacterial activity of the isolates Streptomyces sp. NrASA6 inhibiting the growth of Escherichia coli, Staphylococcus aureus, and Aeromonas sp. NrBF9, as well as the optimal for the test bacteria. The methods used in the antibacterial test are the agar diffusion method with pits and the swabbing method on the surface of medium MHA. The test treatment included incubation on time for Streptomyces sp. NrASA6, divided into 10, 15, 20, and 25 days. The tests were conducted at incubating temperatures of 30 °C and the diameter of the clear zone for 24 and 48 hours. The results of this research were that Streptomyces sp. NrASA6 made slowly for the patogenic bacterial Aeromonas sp. NrBF9 with a diameter of 16.97±1.15 mm for 24 hours, while an inhibition zone did not form on Escherichia coli and Staphylococcus aureus bacteri. The characteristic inhibiton of culture extract 15 days for Streptomyces sp. NrASA6 is bacteriostatic. The incubation period of Streptomyces sp. NrASA6 is influential in the stationary phase, namely 15th days after incubation.